PENYAKIT BERCAK DAUN PADA BIBIT BITTI (Vitex cofassus Reinw.) DI PERSEMAIAN - Faisal Danu Tuheteru; Sri Utami; Illa Anggraeni; Husna Husna; Agus Kurniawan (Jurnal Pemuliaan Tanaman Hutan, 2021)
Bitti (Vitex cofassus Reinw.) is a native plant species in Sulawesi which belongs to Verbenaceae family. This species has great potential to be developed as a house construction material, boat base material, and household utensils. Development of bitti silviculture techniques is very necessary in supporting the efforts to develop these plants. One of problems in this cultivation is disease attack. This study aimed to determine symptoms of disease attack, level of severity, determine kind of pathogen that cause disease, and analyze some factors that cause pathogen attack on bitti seedlings. The results showed that leaf spot disease was found on bitti seedlings with level of severity 33.22%. The identification results showed that the pathogen causing leaf spot disease is the fungus, namely Curvularia sp. Microclimate conditions such as temperature and humidity assumed to affect the emergence of pathogen on bitti seedlings. The attack of Curvularia sp tends to affect the growth of bitti seedlings.